Collaborative Governance: Illegal Parking and It is Management - Nurahman, Reza; Fatimah, Siti; Pizah, Azhar Nur Aulia; Khumayah, Siti; Rahmayanti, Rahmayanti (Indonesian Journal of Advanced Research, 2025)
The rapid economic growth in Cirebon City, especially in the trade and service sectors, is not balanced by the availability of adequate parking lots, thus causing an increase in illegal parking that disrupts traffic order. This study aims to analyze the application of collaborative governance in dealing with the problem of illegal parking in Cirebon City, especially in traffic order areas such as Jalan Dr. Sudarsono and Jalan Dr. Cipto Mangunkusumo. The method used in this study is a descriptive qualitative approach, with data collection techniques through observation of illegal parking locations, in-depth interviews with stakeholders, and document studies related to parking policies. The data obtained were analyzed using Ansell & Gash's collaborative governance model, which includes four dimensions: initial conditions, institutional design, facilitative leadership, and collaborative processes, which are further classified in a hexahelix framework (government, private, academic, community, mass media, and society). The results of the study show that the collaboration carried out by the Parking Unit with various stakeholders has not run optimally, due to: (1) weak coordination between agencies, (2) limited resources in regulatory enforcement, (3) lack of active participation of several hexahelix elements in the decision-making process, and (4) the absence of strict sanctions against illegal parking violators. This study recommends the need to strengthen the role of facilitative leadership and increase the effectiveness of collaborative processes through regular discussion forums and feedback mechanisms involving all elements of hexahelix.